Edukasi Penggunaan Tablet Fe pada Remaja Putri dan Pemeriksaan HB di Dayah Terpadu Al-Madinatuddiniyah Syamsuddhuha Kecamatan Dewantara Kabupaten Aceh Utara - Jasmiati, Jasmiati; Prihatin, Nova Sumaini; Rosyita, Rosyita (Jurnal Abdimas Kesehatan (JAK), 2024)
The health of adolescent girls greatly determines the success of health development, especially in efforts to produce the quality of the nation's future generation in the future because adolescent girls are prospective mothers who will become pregnant and give birth to a baby. The prevalence of anemia in the world ranges from 40-88% and the incidence of anemia in adolescent girls in developing countries is around 53.7%. Basic Health Research Data (Riskesdas) in 2018 shows that the prevalence of anemia in Indonesia in women is 27.2% and in men it is 20.3%. Anemia is more common in young women, namely 32.0% in the 15-24 year age group. The problem encountered is that information about Fe  tablets is still limited, while the iron requirements of adolescent girls are higher than those of adolescent boys, because it is needed to replace iron lost during menstruation and prevent anemia in future mothers-to-be. The aim of this community service is to increase the knowledge of young women about using Fe  tablets and carrying out Hb checks at Dayah Terpadu Al-Madinatuddiniyah Syamsuddhuha, Dewantara District, North Aceh Regency. The method for implementing community service activities lasts 3 days, namely the first day begins with a pre-test followed by providing material on the use of Fe  tablets, on the second day an Hb examination is carried out and on the third day there is a distribution of Fe  tablets and a post-test. The results obtained were an increase in knowledge in the pre-test evaluation, good knowledge from 60% to 90% in the post-test evaluation, and the majority of Hb examination results were not anemia, namely 93%. It is hoped that young women will continue to increase information about the use of Fe  tablets and be obedient in consuming Fe  tablets and carrying out regular Hb checks.